Pengaruh Motivasi, Persepsi, Sikap terhadap Keputusan Pembelian Ban di Toko Sumber Ban - Susanto, Jenny; Juwita, Ratna (MDP Student Conference, 2025)
This study aims to determine and analyze the influence of motivation, perception and attitude on tire purchasing decisions at Toko Sumber Ban Km 3.5. The analysis technique applied in this study is multiple linear regression. Based on the findings of the study, it is explained that the motivation and attitude variables have a significant partial effect on purchasing decisions at Toko Sumber Ban, while the perception variable does not have a significant partial effect on purchasing decisions at Toko Sumber Ban. The motivation, perception, and attitude variables have a significant effect in the simultaneous context on purchasing decisions at Toko Sumber Ban.